Cross-modal Reinforcements in Phonetics Teaching and Learning: An Overview of Innovative Trends in Pronunciation Pedagogy - Wrembel, Magdalena (My University, 2011)
The present contribution provides an overview of some innovative approaches to pronunciation pedagogy, focusing on cross-modal reinforcements aimed at facilitating the process of L2 phonological perception and production. The paper starts with a brief introduction into recent theories of multisensory integration and proceeds with practical suggestions for multimodal reinforcements integrating visual, auditory, kinaesthetic and metacognitive domains of L2 pronunciation teaching and learning. The proposal includes sensory stimulations in the form of articulatory warm-up exercises, assigning vivid symbolic characteristics to target language sounds, phonetic colour coding and the development of conscious metacognitive phonetic strategies.
Keywords: pronunciation teaching; multimodal reinforcement